Bulk growth of undoped and Nd3+ doped zinc thiourea chloride (ZTC) monocrystal: Exploring the remarkably enhanced structural, optical, electrical and mechanical performance of Nd3+ doped ZTC crystal for NLO device applications. (1st May 2017) - Anis, Mohd; Muley, Gajanan.G.
Abstract: In current scenario good quality crystals are demanded for NLO device application hence present communication is aimed to grow bulk crystal and investigate the doping effect of rare earth element Nd 3+ on structural, linear-nonlinear optical, luminescence, mechanical and dielectric properties of zinc thiourea chloride (ZTC) crystal. The ZTC crystal of dimension 21×10×8 mm 3 and the Nd 3+ doped ZTC crystal of dimension 27×17×5 mm 3 have been grown from aqueous solution by slow evaporation technique. The elemental analysis of Nd 3+ doped ZTC single crystal has been performed by means of energy dispersive spectroscopic technique. The powder X-ray diffraction technique has been employed to confirm the crystalline phase and identify the effect of Nd 3+ doping on structural dimensions of ZTC crystal. The grown crystals have been characterized by UV–Vis–NIR study in the range of 190–1100 nm to ascertain the enhancement in optical transparency of ZTC crystal facilitated by dopant Nd 3+ . The recorded transmittance data has been utilized to investigate the vital optical constants of grown crystals. The second order nonlinear optical behavior of grown crystals has been evaluated by means of Kurtz-Perry test and the second harmonic generation efficiency of Nd 3+ doped ZTC crystal is found to be 1.24 times higher than ZTC crystal. The luminescence analysis has been performed to examine the electronic purity and the color centered photoluminescence emission nature of pure and Nd 3+ doped ZTC crystals. The influence of Nd 3+ ion on mechanical behavior of ZTC crystal has been investigated by means of microhardness studies. The nature of dielectric constant and dielectric loss of pure and Nd 3+ doped ZTC crystal has been examined in the range of 40–100 °C under dielectric study. The Z-scan technique has been employed using the He-Ne laser to investigate the third order nonlinear optical (TONLO) nature of Nd 3+ doped ZTC single crystal. The magnitude of TONLO susceptibility, absorption coefficient and refraction has been determined using the Z-scan transmittance data. Graphical abstract: Highlights: Growth of ZTC (21×10×8 mm 3 ) and Nd 3+ doped ZTC (27×17×5 mm 3 ) bulk crystal is achieved. Nd 3+ doped ZTC crystal is excellent TONLO crystal with χ 3 of magnitude 5.82×10 −3 esu. Doping of Nd 3+ significantly improved the optical parameters of ZTC crystal. Enhanced SHG efficiency of Nd 3+ doped ZTC crystal is 1.24 times that of ZTC crystal. Lower dielectrics of Nd 3+ doped ZTC crystal are vital for optoelectronics applications.